Free sensate medial plantar flap for contralateral plantar forefoot reconstruction with flap reinnervation using end‐to‐side neurorrhaphy: A case report and literature review. Issue 3 (24th January 2013) - Lykoudis, Efstathios G.; Seretis, Konstantinos; Lykissas, Marios G.
Abstract: Reconstruction of weight‐bearing plantar defects remains a challenge due to the unique characteristics of the plantar skin and thus the limited available options. The medial plantar flap, either pedicled or free, represents an ideal option, but its use as sensate flap for forefoot defects has been scarcely reported. We present a case of plantar forefoot reconstruction with a free sensate medial plantar flap, with end‐to‐side coaptation of the cutaneous sensory fascicles of the flap to the medial plantar nerve of the recipient. Last follow‐up, at 2 years post‐op, verified a very good functional and aesthetic outcome, indicating that the suggested approach may prove the treatment of choice in selected cases of plantar forefoot reconstruction. © 2013 Wiley Periodicals, Inc. Microsurgery, 2013.